Implementation of the principles of academic integrity as an effective tool for ensuring the quality of higher education - Palamar, Svitlana; Naumenko, Maryna (Educological discourse, 2022)
The article describes the moral and ethical values and legislative norms governing the observance of academic integrity. The opinions of scientists regarding the reasons for violating the rules of academic integrity are summarized. The survey of students of pedagogical specialties of the first (bachelor's) and second (master's) levels of full-time higher education of the Faculty of Pedagogical Education of Borys Grinchenko Kyiv University was conducted, during which the reasons for violations of academic plagiarism (in particular, copying and outsourcing of tasks) by students of higher education institutions were found out; the main ways of overcoming violations of the rules of academic integrity are defined; effective methods of forming a conscious attitude to academic culture in education were found out, among which the most effective was the involvement of students in the activities of the Scientific Society of students, postgraduates, doctoral students and young scientists of the University.